THE IMPACT OF GOVERNANCE EFFECTIVENESS AND COMPANY SIZE ON ENVIRONMENTAL PERFORMANCE - Sofia, Irma Paramita (EAJ (Economic and Accounting Journal), 2019)
In making rational decisions, investors need complete, accurate, and timely information. Companies can disclose information such as the implementation of good corporate governance, financial performance, and sustainability report. This research aims to obtain evidence that good corporate governance and corporate size have an effect on environmental performance. We use sustainability reporting disclosure as a proxy for the environmental achievement of the company. This study indicates that (1) good corporate governance has no effects on environmental performance; (2) corporate size has no effects on sustainability report disclosure.